Enchancing coaches' professional development through a goal setting program : an action research cross-case study - Erkina, Elena; Kiens, Kristel (2013)
Erkina Elena, Kiens Kristel, 2013. Enhancing Coaches’ Professional Development Through a Goal Setting Program: An Action Research Cross-Case Study. Master’s Thesis in Sport and Exercise Psychology. Department of Sport Sciences, University of Jyväskylä. 115 p.